Complications and 30‐day hospital readmission rates of patients undergoing tracheostomy: A prospective analysis. (23rd May 2017) - Spataro, Emily; Durakovic, Nedim; Kallogjeri, Dorina; Nussenbaum, Brian
Abstract : Objective: To determine inpatient and outpatient tracheostomy complication rates and 30‐day hospital readmission rates, and to assess patient and procedural risk factors associated with complications and readmissions. Study Design: Prospective cohort study. Methods: Adult patients undergoing tracheostomy at a single academic hospital performed by any service, for any indication, were enrolled in this study over the course of 1 year. All patients had complete 30‐day follow‐up after discharge to determine complication and hospital readmission rates. Logistic regression was used to assess patient and procedural risk factors associated with these events. Results: One hundred patients were enrolled in this study from June 1, 2015, to June 1, 2016. The overall inpatient tracheostomy complication rate was 47% (95% confidence interval [CI], 37%–57%). Inpatient complications were associated with location in the medical intensive care unit and increased length of hospitalization. The outpatient tracheostomy complication rate was 15% (95% CI, 8%–22%). Outpatient complications were associated with having a previous tracheostomy or an awake tracheostomy under local anesthesia. The all‐cause 30‐day hospital readmission rate was 33% (95% CI, 24%–42%), and the tracheostomy‐specific readmission rate was 13% (95% CI, 6%–20%). All‐cause readmissions were associated with diabetes, length of hospitalization after tracheostomy, and outpatient complications. The overall mortality rate during the study period was 11% (95% CI, 5%–17%), with one tracheostomy‐related death. Conclusion: Patients undergoing tracheostomies are at high risk for both inpatient and outpatient complications, as well for 30‐day hospital readmission. Understanding patient and procedural risk factors associated with these events will help guide interventions for quality improvement. Level of Evidence: 2b. Laryngoscope, 127:2746–2753, 2017